2017
DOI: 10.1051/rees/2017047
|View full text |Cite
|
Sign up to set email alerts
|

The importance of surface finish to energy performance

Abstract: Abstract. Power generation in solar energy systems, thermal control in buildings and mitigation of the Urban Heat Island problem, are all sensitive to directional response to incoming radiation. The radiation absorption and emission profile also plays a crucial role in each system's response and depends strongly on surface finish. This important sensitivity needs wider recognition in materials data sheets, system modeling, plus in materials and environmental engineering. The impact of surface roughness on ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the context of building applications, the cooling performance of radiative cooling coatings on roofs is often assessed using the solar reflectance index (SRI). SRI is determined by considering solar reflectivity and the rate of infrared thermal emission, with higher SRI values denoting more efficient radiative cooling [43]. Advancements in nano-patterning techniques and designer materials are expected to provide a broader knowledge base regarding the radiative properties of different materials [44].…”
Section: Surface Solar Reflectivitymentioning
confidence: 99%
“…In the context of building applications, the cooling performance of radiative cooling coatings on roofs is often assessed using the solar reflectance index (SRI). SRI is determined by considering solar reflectivity and the rate of infrared thermal emission, with higher SRI values denoting more efficient radiative cooling [43]. Advancements in nano-patterning techniques and designer materials are expected to provide a broader knowledge base regarding the radiative properties of different materials [44].…”
Section: Surface Solar Reflectivitymentioning
confidence: 99%
“…Several studies have demonstrated effective radiative cooling and energy saving in buildings. [43][44][45][46] Raman et al fabricated cooling material consisting of seven layers of HfO 2 and SiO 2 , which reflects 97% of incident solar radiation while strongly emitting heat in the ATW 3 Radiative cooling for building exterior. (a) A schematic for a passive radiative cooling system in buildings.…”
Section: Applicationsmentioning
confidence: 99%
“…The ideal radiative cooling materials should simultaneously possess high cooling power, low cost, scalable manufacturing, and contamination resistance characteristics. Previous research showed that rough microstructures could achieve high cooling power and anticontamination because the rough surfaces elevate the thermal emissivity by creating a gradual refractive index change and generating a superhydrophobic surface. , However, nontriviality arises when fabricating the desired microstructures with low cost and scalability because high mid-infrared (mid-IR) emissivity requires high-precision control of the photonic microstructures, where costly and low-yield microfabrication techniques are generally employed (such as photolithography and imprinting). , Thus, innovative manufacturing methods need to be developed to fabricate these microstructures for large-scale applications, such as building energy savings.…”
mentioning
confidence: 99%